Propagación y tuberización in vitro de dos variedades de papa - Araque Barrera, Eyda Johanna; Bohórquez Quintero, María de los Angeles; Pacheco Díaz, José Estiben; Correa Mora, Lenny Yojana; Urquijo Ruíz, Johan Sebastian; Castañeda Garzón, Sandra Liliana; Pacheco Maldonado, José Constantino (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 21-31).